Astma oskrzelowa – objawy, czynniki ryzyka, uwarunkowania genetyczne i diagnostyka - Harvanová, Gabriela; Duranková, Silvia (Alergologia Polska - Polish Journal of Allergology, 2022)
Bronchial asthma is one of the most important diseases of our time in terms of its medical and social consequences. The view of asthma and its treatment is changing considerably. There are several very effective drugs available, the correct administration of which can have a highly beneficial effect on the disease. Asthma is a common chronic disease that affects people of all ages. It is a condition in which the airways narrow and swell and produce extra mucus. This can make it hard to breathe. Asthma can be triggered by allergies, exercise, cold air, emotional stress, or other factors. People with asthma may have shortness of breath, chest tightness, wheezing, and coughing. Asthma can be mild, moderate, or severe. It is a serious condition that can be deadly. There is no cure for asthma, but it can be controlled with medication. This review will discuss our perception of bronchial asthma based on theoretical characteristics such as its triggers, risk factors, symptoms, diagnostic tests, and genetic predisposition. This review will discuss our perception of bronchial asthma based on theoretical characteristics such as its triggers, risk factors, symptoms, diagnostic tests, and genetic predisposition.